Making the case for reusing and sharing data in qualitative consumer research. Issue 2 (4th March 2022) - Rauf, Ateeq Abdul
ABSTRACT: To address the prohibitive cost of qualitative research and to increase the utility and versatility of collected data, this paper puts forth the idea of reusing and sharing qualitative data. This procedure may be employed not only across projects carried out by the same researchers (reuse), but perhaps more importantly also across scholars working separately prior to data analysis (sharing). The paper then notes possible opportunities, important considerations, barriers, benefits, and recommendations for data reuse and sharing.